Bible problems and answers - Hoste, William, d.1938; Rodgers, William 1879-1951; Believers' Magazine (Kilmarnock, Scotland John Ritchie, 1957)
Contents: Answers to "The Question Box", The Believers' Magazine, as contributed to by the authors.
Brethren writers.
Keywords: Bible -- theology; Brethren movement -- theology